1982
DOI: 10.1038/bjc.1982.192
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of collagenase secretion with metastatic-colonization potential in naturally occurring murine mammary tumours

Abstract: Summary.-We report evidence for the secretion of a true mammalian collagenase active against Type 1 collagen, by naturally-occurring mammary tumours of the mouse and show that tumours capable of heavily colonizing the lungs secrete significantly more of this enzyme than those with low pulmonary-colonization potential, or nonneoplastic proliferating (e.g. lactating) mammary tissue. Plasminogen activator is secreted in greater quantity by tumours than by normal tissues, but there is no significant difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This model provided a quantitative assay of tumor cell invasion and demonstrated that natural collagenase inhibitors such as cartilage extract or the purified tissue inhibitor of metalloproteinases (TIMP) both prevented tumor cell invasion of the amnion matrix (23). Additional evidence that collagenolysis facilitates tumor cell invasion was provided by the report of a correlation between collagenase secretion and the metastatic colonization potential in naturally occurring murine mammary tumors (26). Thus immunolocalisation data and in vitro biochemical studies all support the hypothesis that collagen-degrading enzymes play a crucial role in the invasion of connective tissues.…”
Section: Extracellular Enzymesmentioning
confidence: 51%
See 1 more Smart Citation
“…This model provided a quantitative assay of tumor cell invasion and demonstrated that natural collagenase inhibitors such as cartilage extract or the purified tissue inhibitor of metalloproteinases (TIMP) both prevented tumor cell invasion of the amnion matrix (23). Additional evidence that collagenolysis facilitates tumor cell invasion was provided by the report of a correlation between collagenase secretion and the metastatic colonization potential in naturally occurring murine mammary tumors (26). Thus immunolocalisation data and in vitro biochemical studies all support the hypothesis that collagen-degrading enzymes play a crucial role in the invasion of connective tissues.…”
Section: Extracellular Enzymesmentioning
confidence: 51%
“…Plasminogen activator is not unique to tumor cells and many normal cells express the enzyme. Its importance for tumor invasion is uncertain, especially as comparative studies of normal and tumor tissues revealed similar levels of plasminogen activator secretion (30), an observation also reported for murine mammary tumors which demonstrated both high and low pulmonary-colonizing potential (26). However, it has been suggested that the secretion of type IV collagenase concomitantly with plasminogen activator in several tumor cell cultures suggests this is a prerequisite for metastasis-latent collagenase being activated following the conversion of plasminogen to plasmin (31).…”
Section: Extracellular Enzymesmentioning
confidence: 98%
“…Cell suspensions were prepared as described previously (Tarin & Price, 1979 Tarin et al, 1982 for full explanation of the choice of these mathematical methods). In keeping with these decisions the median colonisation grade was used for categorisation of tumour colonisation potential, although results for each inoculated animal are also provided.…”
Section: Methodsmentioning
confidence: 99%
“…This enzyme was also present in serum-free media from a human breast carcinoma cell line ALAB (21) and from a neoplastic epithelial cell line derived from spontaneous rat mammary adenocarcinoma (22). ColLagenase and plasminogen activator have been reported in naturally occurring mammary tumors of the mouse (23) and MCF-7 cells produce collagenolytic activities, able to degrade type I and type IV collagen (24). These findings are consistent with the idea that both interstitial collagenase and type IV collagenase are associated with invasiveness and microinvasive lesions of human breast carcinomas (18,24).…”
Section: Discussionmentioning
confidence: 93%